2012
DOI: 10.5152/akd.2012.033
|View full text |Cite
|
Sign up to set email alerts
|

Survival of patients with well-developed collaterals undergoing CABG or medical treatment: An observational case-controlled study

Abstract: Objective: The effects of coronary artery bypass grafting (CABG) on mortality have not been evaluated in patients with well-developed coronary collaterals. We investigated functional capacity, presence of angina, the occurrence of acute myocardial infarction, survival and mortality in patients with well-developed coronary collaterals both undergoing and refusing CABG. Methods: The study was designed as a retrospective observational case-controlled study. Seventy-eight patients undergoing coronary angiography w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Several studies have shown that adequate CCC is important for smaller myocardial infarct size, fewer ischemic events, and better survival in patients with CAD [3,[9][10][11]. However, similar to the results of Tatlı et al [13] and Caputo et al [14], they showed that the development of CCC was not associated with better outcomes and survival in-hospital and 5 years after CABG surgery. Nathoe et al [12] showed that the presence of collaterals was associated with a significantly lower rate of any first event in the off-pump group.…”
Section: Discussionmentioning
confidence: 56%
“…Several studies have shown that adequate CCC is important for smaller myocardial infarct size, fewer ischemic events, and better survival in patients with CAD [3,[9][10][11]. However, similar to the results of Tatlı et al [13] and Caputo et al [14], they showed that the development of CCC was not associated with better outcomes and survival in-hospital and 5 years after CABG surgery. Nathoe et al [12] showed that the presence of collaterals was associated with a significantly lower rate of any first event in the off-pump group.…”
Section: Discussionmentioning
confidence: 56%
“…In 2019, most of the open-heart operations in Turkey were coronary bypass operations 6 . In our clinic, 78% of the operations were isolated coronary bypass operations.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with acute myocardial infarction, as a treatment principle, patient admission to hospital, early administration of thrombolytic agents, intensive monitoring of the patient in terms of complications of infarction, myocardial oxygen are all needed to reduce the damage risk on the myocardial area [1][2][3] . Today, despite the thrombolytic or interventional cardiologic approaches, many patients undergo coronary bypass surgery (CABG) in patients with ongoing coronary ischemia [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study of patients undergoing coronary angiography collaterals were associated with improved survival in most, but did not influence survival in those treated with subsequent CABG . In another study, investigators found no difference in 5‐year survival in NSTEMI patients with well‐developed coronary collaterals who underwent CABG compared to those who were treated with medical therapy alone .…”
Section: Discussionmentioning
confidence: 99%